Causal explanations for patient engagement with primary care services in Saudi Arabia: a realist review protocol. Issue 4 (26th April 2022) - Alghamdi, Alaa; Abrams, Ruth; Bailey, Julia V; Alves, Paula; Park, Sophie
Abstract : Introduction: Saudi Arabia (SA) has a rapidly developing universal healthcare system which is maturing from its hospital focused origins. However, health service usage suggests that up to 65% of the cases seen in emergency departments were classified as non-urgent and could have been appropriately managed in primary healthcare (PHC) settings. Primary care development in SA has lagged behind secondary care, and evidence suggests that Saudi citizens are currently ambivalent or dissatisfied with their PHC services. Previous research has focused on the quality and patient satisfaction of PHC services in SA. Yet, uncertainty still exists about causal explanations for patient engagement with PHC services and what refinements are needed for PHC. Less attention has been paid to how patient engagement strategies might work differently, which is increasingly recognised as important in PHC services. The aim of this review is to understand the causal explanations for patient engagement with PHC and to generate theory of how the intended outcome of patient engagement with PHC in SA might be achieved through identified contexts and mechanisms. Methods and analysis: A realist review approach will be used to synthesise the evidence. Databases including Medline, EMBASE and CINAHL will be searched. Literature will be included if it has relevance to the research question, and is trustworthy in nature. All document types will be screened including peer reviewed articles, relevant grey literature and related media items. All study types will be included. Stakeholders' feedback will also inform our review. A realist approach is suitable for this review because patient engagement with PHC services is a complex phenomenon. A range of different relevant data will be included in the following stages: developing an initial programme theory, searching the evidence, selecting data, extracting data, synthesising data and refining the programme theory. Ethics and dissemination: This study will use secondary data, and stakeholders are involved only to shape our understanding of the important contexts in patient engagement; hence, a formal ethics review is not required. Findings will be disseminated in a peer-reviewed journal and at relevant conferences. PROSPERO registration number: CRD42020175955.